Coefficient of Uniformity of an Experimental Plot Drill for Different Seed - Patel, S K; Varshney, B P (Journal of Agricultural Engineering, 2007)
The tractor drawn Oyjord plot drill (Wintersteiger) was used to determine the seed distribution pattern for wheat, soybean and Urd. To determine the coefficient of uniformity, three levels of seed rate and four levels of speed of operation (4, 5, 6 and 7 km/h) were used for each crop. The coefficient of uniformity was determined between rows and within rows. The seed rate were 100, 125 and 150 kg/ha, 65, 75 and 85 kg/ha and 12, 15 and 18 kg/ha for wheat, soybean and Urd. respectively. The overall coefficient of uniformity between rows for wheat at a seed rate of 125 kg/ha was 96.97, 95.73, 96.48 and 96.3% at speed of 4, 5.6 and 7 km/h, respectively. The overall coefficient of uniformity between rows for soybean at 75 kg/ha was 95.87, 95.80, 93.81 and 91.98% at 4, 5, 6 and 7 km/h, respectively. The overall coefficient of uniformity between rows for Urd was found maximum i.e. 97.5% at seed rate of 12 kg/ha followed by 15 and 18 kg/ha. The average wheel skid at speed of 4, 5, 6 and 7 km/h was found 5.59, 6.79, 7.61 and 8.51%, respectively. The plot drill was found suitable for sowing of all the three crops.